Takayasu Arteritis: recent advances and clinical pitfalls - E. Tombetti; P. Sarzi-Puttini (Verduci Editore, 2022)
Takayasu arteritis (TA) is a rare idiopathic inflammatory disease of large size arteries, primarily affecting young women. Vasculitic lesions might cause arterial steno-occlusions or dilatation with significant morbidity and mortality. TA rarity may result in its frequent under-recognition and diagnostic delays. Key disease features are systemic inflammation, arterial inflammation and remodelling. They may not always occur together and are differentially targeted by therapies. Accordingly, serial imaging studies are required for exhaustive activity assessment and patient follow-up. The present review provides a practical approach to most frequent clinical pitfalls, including diagnosis, activity assessment, the use of imaging, and the therapeutic approaches, and highlighs the most important unmet needs.